AN ANALYSIS OF IMPLICATURE IN THE KING ARTHUR: LEGEND OF THE SWORD MOVIE - Thoriq Hidayatullah; Adria Vitalya Gemilang; Isti’anatul Hikmah (JOLALI: Journal of Language and Literature, 2023)
This research examines King Arthur: Legend of The Sword. These researchers use Grice’s theory and focus on implicature, such as conventional and non-conventional implicature. This research tried to answer the types of implicature and the function of implicature on Arthur. The research design was qualitative and descriptive to analyze the data. The source of data was script and supported by several instruments. The results of the research were twenty-one data showing conventional and non-conventional implicature. Non-conventional implicature is more pronounced because Arthur often says something different from the truth. Non-conventional implicature usually violates four maxims. It is also supported that Arthur’s speeches violate four maxims. The functions of implicature were representative, directive, and expressive. The most frequent function is the representative function. It happened because it reflects on committing Arthur as the speaker to something being the case, to the truth of the expressed proposition.